Peran Edukasi Kesehatan Dalam Meningkatkan Perilaku Hidup Bersih Dan Sehat Mahasiswa Di Sekolah Tinggi Ilmu Kesehatan Mitra Sejati - Vicky Arfeni Warongan; Rani Cahya; Revi Khairunnisa (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Health counseling is one of the strategic approaches to increase students' knowledge and awareness of the importance of maintaining holistic health which includes physical, mental, social, and reproductive aspects. This activity will be held on March 19, 2025 at Sekolah Tinggi Ilmu Kesehatan Mitra Sejati with interactive lecture methods and educational games "Smart Cards". This study aims to determine the effectiveness of educational methods in improving students' understanding of health issues such as balanced nutrition, personal hygiene, reproductive health, and the dangers of smoking. Through pre-test and post-test analysis of 35 students, a significant increase in participants' understanding was found after participating in counseling. In addition, a fun and participatory approach has been shown to be effective in encouraging active engagement of students, including those who were previously passive. Educational games help to convey material in a more engaging and easy-to-understand way. The results of this activity show that the combination of interactive methods and visual educational media is able to strengthen students' understanding and awareness of the importance of healthy living behaviors. This program has the potential to be replicated in other educational environments to encourage the implementation of a healthy lifestyle among adolescents and students.